LPM3770277, a Potent Novel CDK4/6 Degrader, Exerts Antitumor Effect Against Triple-Negative Breast Cancer - Qiu, Jiahao; Bai, Xinfa; Zhang, Wenjing; Ma, Mingxu; Wang, Wenyan; Liang, Ye; Wang, Hongbo; Tian, Jingwei; Yu, Pengfei (Frontiers in Pharmacology, 2022)
Triple negative breast cancer (TNBC) is a subtype of breast cancer with significant malignancy and poor prognosis but effective treatments are limited. Given the critical role of CDK 4/6 in cell cycle and the apparent success of CDK 4/6 inhibitors against certain cancer, this study attempted to utilize hydrophobic tagging technology to develop a CDK 4/6 degrader against TNBC. We based on the chemical structure of the major metabolite of a clinically approved CDK 4/6 inhibitor, abemaciclib, to synthesize three compounds and evaluated their in vitro cytotoxicity. LPM3770277 stood out as the most promising compound which was further confirmed by a series of binding and CDK 4/6 degradation studies. LPM3770277 was able to bind to CDK 4/6, and time-dependently and dose-dependently increased CDK 4/6 protein degradation. Mechanistic study revealed that LPM3770277 exerted its CDK 4/6 degradation effect via two machineries: proteasome and lysosome-promoted autophagy. Using in vivo TNBC xenograft cancer model, we found that LPM3770277 demonstrated superior anti-tumor efficacy and safety as compared to abemaciclib, although both compounds exerted similar effect on cell cycle arrest. In conclusion, this study for the first time developed and characterized a CDK 4/6 degrader against TNBC using hydrophobic tags, which strongly suggests the viability of hydrophobic tags as a strategy to develop potential treatments against TNBC.